2008
DOI: 10.1017/s000711450899053x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary chia seed (Salvia hispanicaL.) rich in α-linolenic acid improves adiposity and normalises hypertriacylglycerolaemia and insulin resistance in dyslipaemic rats

Abstract: The present study investigates the benefits of the dietary intake of chia seed (Salvia hispanica L.) rich in a-linolenic acid and fibre upon dyslipidaemia and insulin resistance (IR), induced by intake of a sucrose-rich (62·5 %) diet (SRD). To achieve these goals two sets of experiments were designed: (i) to study the prevention of onset of dyslipidaemia and IR in Wistar rats fed during 3 weeks with a SRD in which chia seed was the dietary source of fat; (ii) to analyse the effectiveness of chia seed in improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
119
2
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(147 citation statements)
references
References 42 publications
(74 reference statements)
16
119
2
10
Order By: Relevance
“…Islas-Hernández et al (2007) reported similar values for tortilla fortified with amaranth, 1.4% in tortilla from 100% maize and 1.5% for corn/amaranth tortilla. The fat contents of the chia seed/tortilla were higher than that of the control (Table 1), showing an increase to 200%, that could be attributed to the high concentrations of oil content of the chia seed (Chicco et al 2009;Coates & Ayerza 2009). This is important from the nutritional point of view, chia seed containing a short-chain omega-3 fatty acid, α-linolenic acid (ALA), which has been reported to be useful in the prevention and treatment of coronary artery disease, hypertension, and type 2 diabetes (Simopoulos 1999).…”
Section: Proximate Analysesmentioning
confidence: 90%
See 1 more Smart Citation
“…Islas-Hernández et al (2007) reported similar values for tortilla fortified with amaranth, 1.4% in tortilla from 100% maize and 1.5% for corn/amaranth tortilla. The fat contents of the chia seed/tortilla were higher than that of the control (Table 1), showing an increase to 200%, that could be attributed to the high concentrations of oil content of the chia seed (Chicco et al 2009;Coates & Ayerza 2009). This is important from the nutritional point of view, chia seed containing a short-chain omega-3 fatty acid, α-linolenic acid (ALA), which has been reported to be useful in the prevention and treatment of coronary artery disease, hypertension, and type 2 diabetes (Simopoulos 1999).…”
Section: Proximate Analysesmentioning
confidence: 90%
“…However, the nutritional community's attention has recently been drawn to a novel whole grain, chia seed, whose oil content ranges from 25% to 35% with high concentrations of polyunsaturated fatty acids as well as a complement of vitamins and minerals (Chicco et al 2009;Coates & Ayerza 2009). Whole grains are important sources of many nutrients such as dietary fibre, resistant starch, trace minerals, vitamins, folic acid, selenium, zinc, phenolic compounds, and other compounds including phytoestrogens and antioxidants, which may contribute to the apparent cardioprotective effects of whole grains (Djoussé et al 2007).…”
mentioning
confidence: 99%
“…Salvia species [23][24][25]. The presence of pentacyclic triterpenes (oleanolic acid, carnosic acid, and ursolic acid) in Salvia species may account for the plant PL inhibitory propensities [26][27][28][29]. All in all, pharmacological inhibition of dietary lipid digestion and absorption may induce favorable amelioration of dyslipidemia, atherosclerosis, and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The chia is a herbaceous plant of annual cycle originating from the mountainous regions of central and western Mexico and northern Guatemala (Bueno et al, 2010, Chicco et al, 2009.…”
Section: Introductionmentioning
confidence: 99%